The biology of glass sponges - Leys S.P., Mackie G.O., Reiswig H.M. (Advances in Marine Biology, 2007)
As the most ancient extant metazoans, glass sponges (Hexactinellida) have attracted recent attention in the areas of molecular evolution and the evolution of conduction systems but they are also interesting because of their unique histology: the greater part of their soft tissue consists of a single, multinucleate syncytium that ramifies throughout the sponge. This trabecular syncytium serves both for transport and as a pathway for propagation of action potentials that trigger flagellar arrests in the flagellated chambers. The present chapter is the first comprehensive modern account of this group and covers work going back to the earliest work dealing with taxonomy, gross morphology and histology as well as dealing with more recent studies. The structure of cellular and syncytial tissues and the formation of specialised intercellular junctions are described. Experimental work on reaggregation of dissociated tissues is also covered, a process during which histocompatibility, fusion and syncytialisation have been investigated, and where the role of the cytoskeleton in tissue architecture and transport processes has been studied in depth. The siliceous skeleton is given special attention, with an account of discrete spicules and fused silica networks, their diversity and distribution, their importance as taxonomic features and the process of silication. Studies on particle capture, transport of internalised food objects and disposal of indigestible wastes are reviewed, along with production and control of the feeding current. The electrophysiology of the conduction system coordinating flagellar arrests is described. The review covers salient features of hexactinellid ecology, including an account of habitats, distribution, abundance, growth, seasonal regression, predation, mortality, regeneration, recruitment and symbiotic associations with other organisms. Work on the recently discovered hexactinellid reefs of Canada’s western continental shelf, analogues of long-extinct Jurassic sponge reefs, is given special attention. Reproductive biology is another area that has benefited from recent investigations. Seasonality, gametogenesis, embryogenesis, diVerentiation and larval biology are now understood in broad outline, at least for some species. The process whereby the cellular early larva becomes syncytial is described. A final section deals with the classification of recent and fossil glass sponges, phylogenetic relationships within the Hexactinellida and the phylogenetic position of the group within the Porifera. Palaeontological aspects are covered in so far as they are relevant to these topics.